Harnessing of Banana Ripening Process for Banana Juice Extraction in Uganda - Omulo, Godfrey; Banadda, Noble; Kiggundu, Nicholas (Afr. J. Food Sci. Technol, 2015)
Banana is a very important staple food crop in Uganda. It is grown in every part of the country with the largest production recorded in western and central regions. Uganda is ranked the second largest producer of banana after India in the world. Bananas produced in Uganda are largely consumed locally as matookewith small amounts being exported as green banana or ripened to make juice, wine, beer or chips. There are variousmanual techniques of making banana juices in Uganda ranging from hands, foot and small scale mechanical machines which are not economical and hygienic. However, banana ripening poses a very big challenge to farmers and small scale processors. This has resulted in large quantities of banana loss, reduced shelf life and low economic returns to small scale farmers. In this review, different methods of natural, controlled banana ripening and ripening delay techniques are outlined. Controlled ripening of bananas is a key facet to good economic return in banana production as well as a stable and feasible strategy to ensure constant supply of ripe banana for banana juice processing.
Keywords: Banana, Natural ripening, Controlled ripening, Delayedripening, Shelf life